Combined effects of avasimibe immunotherapy, doxorubicin chemotherapy, and metal–organic frameworks nanoparticles on breast cancer. Issue 5 (29th October 2019) - Lei, Jun; Wang, Hongjian; Zhu, Daoming; Wan, Yibin; Yin, Lei
Abstract: CD8 + T cells play a vital role in cancer immunotherapy and can be shaped by metabolism. Avasimibe is an acyl coenzyme A‐cholesterol acyltransferase (ACAT) inhibitor, which has been clinically verified safe in other phase Ⅲ clinical trials. It can potentiate the killing function of CD8 + T cells by modulating cholesterol metabolism. Doxorubicin (DOX) is an anticancer drug widely used in many cancers to induce tumor cell apoptosis. Unfortunately, DOX also can induce toxic and side effects in many organs, compromising its usage and efficacy. Herein, we report the combinational usage of avasimibe and a safe pH sensitive nano‐drug delivery system composing of DOX and metal–organic frameworks nanoparticles (MNPs). Our findings demonstrated that DOX–MNPs treatment inhibited tumor growth with good safety profile and avasimibe treatment combined DOX–MNPs treatment exhibited a better efficacy than monotherapies in 4T1 breast cancer therapy.